The Population Structure of a Globe Artichoke Worldwide Collection, as Revealed by Molecular and Phenotypic Analyzes - Rau, Domenico; Attene, Giovanna; Rodriguez, Monica; Baghino, Limbo; Pisanu, Anna Barbara; Sanna, Davide; Acquadro, Alberto; Portis, Ezio; Comino, Cinzia (Frontiers in Plant Science, 2022)
Knowledge of the organization of the domesticated gene pool of crop species is an essential requirement to understand crop evolution, to rationalize conservation programs, and to support practical decisions in plant breeding. Here, we integrate simple sequence repeat (SSR) analysis and phenotypic characterization to investigate a globe artichoke collection that comprises most of the varieties cultivated worldwide. We show that the cultivated gene pool of globe artichoke includes five distinct genetic groups associated with the major phenotypic typologies: Catanesi (which based on our analysis corresponds to Violetti di Provenza), Spinosi, Violetti di Toscana, Romaneschi, and Macau. We observed that 17% and 11% of the molecular and phenotypic variance, respectively, is between these groups, while within groups strong linkage disequilibrium and heterozygote excess are evident. The divergence between groups for quantitative traits correlates with the average broad-sense heritability within the groups. Phenotypic divergence between groups for both qualitative and quantitative traits is strongly and positively correlated with SSR divergence (FST) between groups. All this implies low population size and strong bottleneck effects, and indicates a long history of clonal propagation and selection during the evolution of the domesticated gene pool of globe artichoke. Moreover, the comparison between molecular and phenotypic population structures suggests that harvest time, plant architecture (i.e., plant height, stem length), leaf spininess, head morphology (i.e., head, bract shape, spininess) together with the number of heads per plant were the main targets of selection during the evolution of the cultivated germplasm. We emphasize our findings in light of the potential exploitation of this collection for association mapping studies.